Multi-wavelength spectrophotometric determination of peracetic acid and the coexistent hydrogen peroxide via oxidative coloration of ABTS with the assistance of Fe2+ and KI. (January 2022) - Lin, Jinbin; Xiao, Junyang; Cai, Hengyu; Huang, Yixin; Li, Jiawen; Yang, Haoyu; Li, Tao; Zou, Jing
Abstract: In this study, a multi-wavelength spectrophotometric method for simultaneous determination of peracetic acid (PAA) and coexistent hydrogen peroxide (H2 O2 ) was presented. This method was based on the oxidation of 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) with the assistance of Fe 2+ /KI to produce a stable green radical (ABTS ●+ ), which could be determined at four characteristic peaks (i.e., 415 nm, 650 nm, 732 nm, and 820 nm). The absorbances of ABTS ●+ at four peaks were well linear (R 2 > 0.999) with concentrations of both total peroxides (PAA + H2 O2 ) and PAA in the range of 0–40 μM under optimized conditions. The sensitivities for determining total peroxides at 415 nm, 650 nm, 732 nm and 820 nm were determined to be 4.248 × 10 4 M −1 cm −1, 1.682 × 10 4 M −1 cm −1, 2.132 × 10 4 M −1 cm −1, and 1.928 × 10 4 M −1 cm −1, respectively. For determining PAA, the corresponding sensitivities were 4.622 × 10 4 M −1 cm −1, 1.895 × 10 4 M −1 cm −1, 2.394 × 10 4 M −1 cm −1 and 2.153 × 10 4 M −1 cm −1, respectively. The concentration of coexistent H2 O2 was gained by deducting PAA concentration from total peroxides concentration. The ABTS method was accurate enough to determine PAA concentration in natural water samples. Moreover, the ABTS method was successfully used to determine the changes of PAA and coexistent H2 O2 and to distinguish their role on naproxen degradation in heat-activated PAA process. Overall, the ABTS method could be used as an alternative method for the convenient, rapid and sensitive determination of PAA and the coexistent H2 O2 in water samples. Graphical abstract: Image 1 Highlights: The ABTS method was based on the generated ABTS ●+ in Fe 2+ or KI-catalyzed PAA system. The generated ABTS ●+ could be quantified at 415 nm, 650 nm, 732 nm and 820 nm. The ABTS method was reliable, fast and sensitive to determine PAA and coexistent H2 O2 . Water matrices had little impact on the determination of PAA and coexistent H2 O2 . ABTS method was successfully used to monitor the change of PAA in heat/PAA process.